Pengaruh Model Pembelajaran Game Based Learning Menggunakan Media Nearpod Terhadap Capaian Pembelajaran Pengetahuan Siswa Pada Mata Pelajaran IPS di SMPN 33 Surabaya - Fadhilah, Nandita Adhys Nur (Jurnal Dialektika Pendidikan IPS, 2025)
This study aims to analyze the effect of the Game Based Learning (GBL) learning model using Nearpod media on student learning outcomes in Social Sciences (IPS) subjects at SMPN 33 Surabaya. The background of this study is based on the low involvement of students in the conventional learning process which has implications for less than optimal learning outcomes. The GBL model was chosen because it is able to create a more interactive and enjoyable learning atmosphere, while Nearpod is used as an interactive digital media that supports game-based learning. This study uses a quantitative method with a quasi-experimental design, involving two groups, namely the experimental class and the control class. Data were collected through pretest and posttest tests to determine differences in learning outcomes before and after treatment. The results showed that there were significant differences in student learning outcomes between the group using the Nearpod-based GBL model and the group using conventional learning methods. These findings indicate that the application of the Nearpod-based GBL learning model can increase student motivation, involvement, and learning outcomes in IPS subjects. Thus, this model can be used as an alternative relevant learning strategy to improve learning outcomes in the digital era.